16 Prevalence and risk factors for hiv-associated neurocognitive impairment (hand) amongst adults aged 50 and over attending a hiv clinic in northern tanzania. Issue 8 (13th July 2017) - Paddick, Stella-Maria; Flatt, Aidan; Eaton, Patrick; Kellet-Wright, Johanna; Duijinmaijer, Ashanti; Urasa, Sarah; Kisoli, Aloyce; Yarwood, Vanessa; Thornton, Jessica; McCartney, Judith; Irwin, Charlie; Dotchin, Catherine; et al.
Abstract : Objective: HIV infection is a major cause of disease burden and disability across sub-Saharan Africa (SSA). HIV-associated neurocognitive impairment (HAND) is estimated to affect 8 million people with HIV infection across the continent and is associated with increased mortality and morbidity. As a result of demographic transition and increased coverage of combination antiretroviral therapy (cART) the proportion of people aged 50 and over living with HIV infection in SSA is predicted to triple (to over 9 million people by 2040). Despite this, few published data exist on the prevalence of, or risk factors for, HAND in older individuals in SSA. We aimed to estimate prevalence and risk factors for HAND in a stable population of HIV positive individuals under long term follow up at a government clinic in Northern Tanzania, one of the pioneer sites for cART in SSA. Method: A systematic sample of individuals aged 50 and over attending a HIV care and treatment centre for routine follow up were assessed for HAND using a locally normed neuropsychological battery adapted to a low literacy setting. All participants subsequently underwent a clinical interview, neurological examination, informant history for functional impairment and standardised psychiatric screening questionnaire. HAND was defined according the American Academy of Neurology (AAN) 2007 criteria for Asymptomatic Neurocognitive Impairment, Minor Neurocognitive Disorder (MND) and HIV-associated Dementia (HAD). General and HIV-specific risk factors for symptomatic HAND were examined using univariable and multivariable logistic regression. Results: Complete data were available for 227 participants (162 (71%) female, median age 57.9 years) of whom 35% had 4 years formal education or fewer. Median Cd4 count was 500/µl and 95.5% of participants were on cART. Preliminary data indicate that the overall prevalence of HAND was 61.2% (ANI 35.2%, MND 23.8%, HAD 2.2%) and of symptomatic HAND (MND and HAD) 25%. Presence of symptomatic HAND was not related to current or nadir Cd4 count, or time since HIV diagnosis, but was independently associated with older age, illiteracy, living alone and greater number of depression symptoms. Conclusion: HAND was very prevalent in this stable outpatient cohort of older adults most of whom were on cART. Initial results suggest that in this cohort of older adults in SSA, risk factors for symptomatic neurocognitive impairment appeared to be less related to HIV infection and more similar to factors commonly associated with neurodegenerative dementias in both high income and low income country settings.